2*(x+7)=3*(2x-5)

Simple and best practice solution for 2*(x+7)=3*(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2*(x+7)=3*(2x-5) equation:


2*(x+7)=3*(2x-5)

We simplify the equation to the form, which is simple to understand
2*(x+7)=3*(2x-5)

Reorder the terms in parentheses
+(+2x+14)=3*(2x-5)

Remove unnecessary parentheses
+2x+14=+3+*(+2x-5+)

Reorder the terms in parentheses
+2x+14=+(+6x-15)

Remove unnecessary parentheses
+2x+14=+6x-15

We move all terms containing x to the left and all other terms to the right.
+2x-6x=-15-14

We simplify left and right side of the equation.
-4x=-29

We divide both sides of the equation by -4 to get x.
x=7.25

See similar equations:

| 6-5x=4x+6 | | 6x-9=9-9x | | x+10=-2x+46 | | 5(x)+5=30 | | =9q^8+16r^2 | | =16z^2-40z+25 | | .5x+4=0.6 | | -33=-3x-5x+7 | | 51=3x+3x+9 | | 3x-19y=11 | | 5x+5+7x=77 | | =56*w^2-86*w+20 | | 36=5(x)+6 | | 2-3(x+4)=9-(3-2x) | | h=125t-16t^2 | | x-.05=2x | | 16y=80 | | =5*t^6+23*t^3*x+12*x^2 | | =5*t^6+23*t^3+12*x^2 | | w+6=4 | | v-5=-6 | | (y/3)-7=4 | | 6+8(x+2)=6 | | X(5)=325 | | -2(x-3)+5x+7=3(4-3x)+12x-9 | | X(6)=312 | | =7*x^2-29*x-30 | | -2X+7=0 | | 6x-12=-36 | | (X/4)+9=13 | | =x^2-3*x-28 | | =8*y^3+3*y^2-56*y-21 |

Equations solver categories